2020
DOI: 10.3390/microorganisms8010119
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Antibacterial, Antioxidant, and Anti-Inflammatory Properties by Drying of Prunus domestica L. Plum Juice Extracts

Abstract: The consumption of plums in a fresh form is seasonal, therefore the transformation of plum juice extracts into powdered form is a good alternative for its longer availability throughout the year. The drying process can moderate the physical and chemical properties of the plum extracts, thus, this study examined the changes in biological activity, i.e., antibacterial, antioxidant, and anti-inflammatory properties moderated by freeze, vacuum, and spray drying. It was suggested that the drying processes and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 47 publications
(67 reference statements)
1
8
0
Order By: Relevance
“…Cytotoxicity of olive-leaf extracts was evaluated previously to the antioxidant and anti-inflammatory assays. MTT (3,4,5-dimethylthiazol-2,5-diphenyl-tetrazolium bromide) (Sigma, Madrid, Spain) reduction assay was used to determine AGS cell viability [ 38 ]. Confluent cell cultures (~90%) were trypsinized (Trypsin/EDTA 170,000 U/L) (Lonza) and cells were seeded (~5 × 10 4 cells per well) in 96-well plates (Sarstedt) and incubated in culture medium at 37 °C under 5% CO 2 in a humidifier incubator for 24 h. Serum-free medium containing the extracts (at 2 mg/mL final concentration) was used to replace cell culture medium, and cells were incubated at 37 °C under 5% CO 2 for 24 h. Non-treated cells (experimental control) were incubated in serum-free medium without extracts.…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxicity of olive-leaf extracts was evaluated previously to the antioxidant and anti-inflammatory assays. MTT (3,4,5-dimethylthiazol-2,5-diphenyl-tetrazolium bromide) (Sigma, Madrid, Spain) reduction assay was used to determine AGS cell viability [ 38 ]. Confluent cell cultures (~90%) were trypsinized (Trypsin/EDTA 170,000 U/L) (Lonza) and cells were seeded (~5 × 10 4 cells per well) in 96-well plates (Sarstedt) and incubated in culture medium at 37 °C under 5% CO 2 in a humidifier incubator for 24 h. Serum-free medium containing the extracts (at 2 mg/mL final concentration) was used to replace cell culture medium, and cells were incubated at 37 °C under 5% CO 2 for 24 h. Non-treated cells (experimental control) were incubated in serum-free medium without extracts.…”
Section: Methodsmentioning
confidence: 99%
“…Plums are rich in phenolic compounds which are associated with various bioactive potentials including antibacterial effect. Freeze dried plum powder extract was reported to inhibit the growth of various Gram positive and Gram negative bacteria [ 40 ]. Valtierra-Rodríguez et al [ 41 ] reported that the plum fruit extract restricted the growth of Campylobacter jejuni and Campylobacter coli in poultry skin inoculated with these pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…For the anti-inflammatory activity evaluation, murine macrophage cell line RAW264.7 was used. The assay was carried out following the procedure described by Silvan et al [ 24 ]. Briefly, cells were seeded (~5 × 10 4 cells/well) in 96-well plates (Sarstedt) and incubated in complete cell culture medium at 37 °C under 5% CO 2 in a humidifier incubator for 24 h. For treatments, cells were incubated with the raw samples and the gastric digestates (1.5 mg/mL) were reconstituted in serum-free medium at 37 °C under 5% CO 2 for 120 min.…”
Section: Methodsmentioning
confidence: 99%